Służby miejskie na ratuszu w miastach Wołynia w XVI–XVII w. - Biłous, Natalia (Roczniki Dziejów Społecznych i Gospodarczych, 2015)
Town halls in the cities of the Wołyń region in the modern era (Summary) The article presents source material on town halls found in the towns of the Wołyń region. The first references to the town halls in question date back to the sixties of the sixteenth century. Prior to their appearance the meetings of the judicial authorities were held in the Mayor’s house which, in the seventeenth century, was the second most important public building in the town. As such, it served as a courtroom hosting jury trials. Town halls in the Wołyń region were made of wood, and it was not until the latter half of the seventeenth century that town halls made of brick or stone began to appear. However, these buildings did not even survive until the eighteenth century, and, unfortunately, no image of these edifices is preserved today. The way in which the towns of the region functioned was significantly affected by a group of men remaining in the service of the municipal authorities. Among the latter, to whom references are made in our sources, are: the servants of mayors and deputy mayors, the town crier, the executioner, night watchmen, town hall guardians and town guards. In addition to having underdeveloped municipal services, the towns of the region in question were administered along less complex lines than those following the administration of the other towns of the Old Poland, which can be taken to indicate the underdevelopment of both their municipal economies and their self-government as well. However, there can be no doubt that in employing town servants municipal authorities in the region, in the sixteenth and seventeenth centuries, took into consideration the financial possibilities of the town budget.